2015
DOI: 10.3141/2472-07
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Amazon Basin Forest Roads Manual

Abstract: A forest roads manual is being written to aid the Brazilian Forest Service in its tropical forestry operations and timber sale concessions in the Amazon basin. The objective of the manual is to develop standards, guidelines, and operational information that will help forest road operations meet best management practices. The manual includes information on transportation planning in conjunction with strategic and tactical timber sale planning; road design; road drainage considerations; roadway materials use; sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…From the documents studied, only Keller et al [28] consider a clear form of forest road classification. Keller et al [28] analyze the content of the Amazon Basin Forest Roads Manual, which aims to develop standards and guidelines for forest road operations.…”
Section: Discussionmentioning
confidence: 99%
“…From the documents studied, only Keller et al [28] consider a clear form of forest road classification. Keller et al [28] analyze the content of the Amazon Basin Forest Roads Manual, which aims to develop standards and guidelines for forest road operations.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, despite its logistical shortcomings, AM2 is a robust, proven system that continues to serve a critical role in sustaining forceprojection capabilities. While the armed forces have historically been the primary clients of portable matting systems, the potential to extend its application in certain cases to supporting civil infrastructure and civilian rapid response operations for lightweight aircraft and ground support vehicles should not be discounted (3,4). Additional improvements in modeling and full-scale evaluation capabilities will continue to increase end-user confidence and ensure safe operation for both civil and military flight operations.…”
Section: Computationally Efficient Modeling Of Lightweight Expedition...mentioning
confidence: 99%
“…Tropical residual soils, especially lateritic deposits, which have been the subject of research in the Amazonia for use in road paving, can also be identified [47,60,108,109] due to their peculiarities in comparison to sedimentary soils, as previously described. Keller et al [110] stated that the materials commonly used in the Amazonia region for road paving include local laterite deposits but that despite being a hard and cemented material, they may still contain a high clay content. As a paving material, it is widely used for the structural layers of highways, but the first challenge is to locate the deposits with an adequate quantity and quality of the material.…”
Section: Use Of Wooden Piles For the Construction Of A Road Embankmen...mentioning
confidence: 99%
“…Figure 20.Use of wood in the drainage of igarapés crossing roads with low traffic volume in the Brazilian Amazonia. (a)Wooden bridge (pinguela); (b) hollow wood "tube"[110].…”
mentioning
confidence: 99%